Analysis of the preparation of commercial negotiations of fast-moving consumer goods companies in Portugal = Análise da preparação de negociações comerciais de empresas de produtos de grande consumo em Portugal - Falcão, P. F.; Reis, C. (International Business and Economics Review, 2014)
The current business environment is characterized by globalization, technological development, strong competition, plus the growing need to identify opportunities and optimize resources. To succeed in this context, organizations require their executives to have excellent management skills particularly in the area of negotiation. There is a broad consensus in the scientific community about the importance of preparing for the negotiations as an essential step in determining a successful outcome (Thompson, 2008; Lewiki, Saunders & Minton, 1999; Ury, 1991; Kennedy, Benson & McMillan, 1986). This work aims to examine how executives of fast-moving consumer goods companies in Portugal prepare their commercial negotiations, and to identify differences that may exist between national and multinational companies. This study was based on literature research and on personal interviews conducted in 22 companies that altogether have a total turnover of approximately 3 billion euros, which is very representative of the large consumer goods sector in Portugal. The main conclusion of the study is that there are several areas of possible and desirable improvement, both in the evaluation of each of the parties and the circumstances in which negotiation takes place, as well as in their strategic and tactical planning.